Carlos P. Garcia an annotated bio-bibliography, 1957-1971 - Barraquiel, Josefina A. (1974)
This annotated bio-bibliography of Carlos P. Garcia, fourth President of the Republic of the Philippines, compiles and annotates works by and about Garcia published from the beginning of his tenure as President of the Philippines in 1957 to the time of his death in 1971. It consists of three chapters: Chapter I is the Introduction; Chapter II is the Biography of Carlos P. Garcia; and Chapter III is the Bibliography proper.